Interventions to improve the health and wellbeing of older people living alone: a mixed-methods systematic review of effectiveness and accessibility. Issue 7 (7th July 2021) - Johnstone, Georgina; Dickins, Marissa; Lowthian, Judy; Renehan, Emma; Enticott, Joanne; Mortimer, Duncan; Ogrin, Rajna
Abstract: The global population is ageing and the likelihood of living alone increases with age. Services are necessary to help older people living alone to optimise health and wellbeing. This systematic review aimed to summarise the effectiveness and accessibility of interventions to improve the health and wellbeing of older people living alone. Relevant electronic databases (CINAHL, MEDLINE, PsycINFO and Scopus) were searched for all years up to August 2018. Studies were included if they involved older people (aged ⩾55 years) living alone, and an intervention with measured health and wellbeing outcomes. All study types were included. The Theory of Access was used to assess interventions across dimensions of accessibility, availability, acceptability, affordability, adequacy and awareness. Twenty-eight studies met the eligibility criteria; 17 studies focused on ageing safely in place and 11 on psychological and social wellbeing. Studies comprised quantitative (N = 19), qualitative (N = 4) and mixed-methods (N = 5) approaches. Dimensions from the Theory of Access were poorly addressed in the studies, particularly those of higher-quality methodology. Studies were heterogeneous, preliminary in scope and lacked consistent study design, methodology or measurement. Services that do not address user accessibility in design or evaluation may be limited in their uptake and impact. It is recommended that dimensions of access and co-creation principles be integrated into service design processes and be evaluated alongside clinical effectiveness.